Peningkatan Kemampuan Membaca Kitab Kuning Melalui Pembelajaran Arab Pegon - Bashirotul Hidayah (Fakultas Tarbiyah Institut Agama Islam Bani Fattah Jombang, 2019)
Abstract: Pesantren will not be separated from the mastery of the yellow book. To understand this, an approach was taken. The learning of the yellow books in pesantren many still use the traditional approach of using Arabic pegon as the target language in translating. This study aims to determine the application of learning, supporting factors and obstacles in increasing the ability to read the yellow book through Arabic pegon learning in Madrasah Tsanawiyah Al Anwar Cangkringrandu Perak Jombang. This research is a qualitative research. The data source of this research is primary data & secondary data obtained from Madrasah Tsanawiyah Al Anwar Cangkringrandu Perak Jombang. Data collection techniques used in this study were observation, interview and documentation. Analysis of the data used in this research is descriptive analysis ,. The results of this study indicate that. First: the process of teaching reading the yellow book with Arabic pegon reveals three things namely the content or message, linguistic elements and extraliungistic elements of the text. Second: the inhibiting factors of yellow book teaching with Arabic pegon in Madrasah Tsanawiyah Al Anwar Cangkringrandu Perak Jombang which include linguistic factors including morphological and siktasis and non-linguistic factors include lack of mastery of the source language and target language. Third: The advantages of teaching yellow books with Arabic pegon in Madrasah Tsanawiyah Al Anwar Cangkringrandu Perak Jombang include: a) showing all the elements of the existing text, b) students can know the position of each sentence, c) get a lot of vocabulary, d) preserve the treasury of the archipelago.